If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14x + -15 = -43 Reorder the terms: -15 + -14x = -43 Solving -15 + -14x = -43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -14x = -43 + 15 Combine like terms: -15 + 15 = 0 0 + -14x = -43 + 15 -14x = -43 + 15 Combine like terms: -43 + 15 = -28 -14x = -28 Divide each side by '-14'. x = 2 Simplifying x = 2
| 8x+4(1.5x)=250 | | K(k+4)=0 | | 3(30+s)=4(s+1s) | | 13x-1=x+27 | | 5/3x:3/1 | | -9(x+3)+4x+5=6x+12 | | 8(31.25+-0.5y)+4y=250 | | 3(30+s)=4(s+1a) | | 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 |